Best Friends - Wilson, Jacqueline; Illustrated by Sharratt, Nick (London Corgi Yearling, 2004)
Gemma and Alice were born on the same day and have been devoted best friends ever since. Despite Gemma's larger-than-life personality and Alice's quieter, calmer character, the two are inseparable - until Alice has to move house, all the way to Scotland.
Include illustrations
Keywords: Best friends -- Friendship -- England